2015
DOI: 10.1186/s11671-015-1206-7
|View full text |Cite
|
Sign up to set email alerts
|

Complex of C60 Fullerene with Doxorubicin as a Promising Agent in Antitumor Therapy

Abstract: The main aim of this work was to evaluate the effect of doxorubicin in complex with C60 fullerene (C60 + Dox) on the growth and metastasis of Lewis lung carcinoma in mice and to perform a primary screening of the potential mechanisms of C60 + Dox complex action. We found that volume of tumor from mice treated with the C60 + Dox complex was 1.4 times less than that in control untreated animals. The number of metastatic foci in lungs of animals treated with C60 + Dox complex was two times less than that in contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 29 publications
0
37
0
2
Order By: Relevance
“…However, during the past five years the complexation of pristine C60 fullerene with small drug molecules in aqueous solution has become a major focus of scientific investigation. In part, this is due to recent successes in combining co-administered C60 fullerene with antitumor drugs, resulting in improvement of medico-biological effects both in vivo and in vitro [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…However, during the past five years the complexation of pristine C60 fullerene with small drug molecules in aqueous solution has become a major focus of scientific investigation. In part, this is due to recent successes in combining co-administered C60 fullerene with antitumor drugs, resulting in improvement of medico-biological effects both in vivo and in vitro [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…For .25 years, derivatives of this class of NP have served as a platform for a variety of biomedical applications including X-ray and magnetic resonance imaging (MRI) contrast agents, [3][4][5][6] drug delivery, [5][6][7][8][9][10][11][12][13] antioxidant neuroprotection,…”
Section: Introductionmentioning
confidence: 99%
“…For addressing these impediments, novel complex of the classical and highly active anticancer drug Cis with FC 60 was prepared and analyzed. Previous studies on FC 60 demonstrated its good biocompatibility and potential suitability to be used as delivery platform for another golden chemotherapy standard -namely Dox [29,30].…”
Section: Resultsmentioning
confidence: 99%
“…Recently we have demonstrated that anticancer drugs with anaromatic core may form non-covalent complexes with FC 60 in physiological solution [26,27], which was suggested to be a key process leading to amplification of the antitumor effect of antibiotic doxorubicin (Dox) in vitro towards various tumor lines and in vivo towards C57BL/6J male mice bearing Lewis lung carcinoma [28][29][30]. Based on these results, we hypothesized that the anticancer effects of other drugs may also be enhanced by their immobilization on FC 60 [27,31], and selected Cis as a potential candidate for conjugation on this novel nanocarrier.…”
Section: Introductionmentioning
confidence: 99%